COUNTERPRODUCTIVE WORK BEHAVIOR: PENGARUH JOB DEMAND DAN KNOWLEDGE MANAGEMENT - Gusti Putu Devandra Yudhistira; Dewi Khrisna Sawitri (JURNAL LENTERA BISNIS, 2025)
The study highlights the impact of job demand and knowledge management in the company towards the counterproductive work behavior of drivers and co-drivers in a bus company. Conducted at PT Gunung Harta Transport Solutions, Malang, Indonesia, the research involved 79 bus crew consists of drivers and co-driver that are selected through simple random sampling from a population of 382 crew. Data for the research were collected via questionnaire and analyzed using the Structural Equation Model Partial Least Square (SEM-PLS) method. The result reveal that knowledge management had a significant negative impact towards counterproductive work behavior and that job demand positively and significantly influence counterproductive work behavior. These findings can be valuable for human resource management to manage and mitigate employee’s counterproductive work behavior with the help of a good knowledge management and the right amount of job demand.